Rubber material for high-non-slip high-wear-resistance shoe outsole and preparation method thereof
By constructing a multi-glue-generating system with good thermodynamic compatibility, combined with modified four-point zinc oxide whiskers and high specific surface area white carbon black, the problem of rubber materials in the prior art is difficult to take into account both slip resistance and wear resistance. It achieves a balance between high slippage and high wear resistance.
Patent Information
- Application Number
- CN202411475178.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-31
AI Technical Summary
While improving the anti-slip performance of shoe soles, existing rubber materials are difficult to maintain good wear resistance. The modification effect of white carbon black is closely related to the rubber formula refining reaction process. If the modification conditions are not appropriate, it will be Causes loss of wear resistance.
Using different glue types with good thermodynamic compatibility, a multivariate glue system was constructed, and a modified four-point zinc oxide whisker and high specific surface area precipitation method were introduced. The three-dimensional four-point needles were modified by silane coupling agent. whiskers improve their dispersion and bonding properties. Combined with high cis polybutadiene rubber and styrene butadiene rubber, a rubber formula that takes into account both anti-slip and wear resistance is designed.
Achieving the balance of high slippage and high wear resistance, avoiding wear resistance loss caused by rubber compatibility problems, and improving the dispersion of whiskers and rubber molecular chains through silane coupling agent modification The bonding force ensures high performance of the material.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber compositions, and in particular to a rubber material for a high-slip and high-wear-resistant shoe outsole and a preparation method thereof. Background Art
[0002] Slipping is one of the important factors causing personal injury, especially in workshop production environment, which can easily cause serious production accidents; when the friction between shoes and contact surfaces is insufficient, it is easy to slip during exercise. There are many factors that affect slipping, such as environmental factors, ground factors, human factors and shoe factors, among which environmental factors, ground factors and human factors are unpredictable, while shoe factors are more controllable; further speaking, the anti-slip performance of shoes is mainly controlled by outsole materials and outsole patterns; materials are the basic factors to improve anti-slip performance, and outsole pattern design is an important factor to improve anti-slip performance.
[0003] At present, the materials commonly used for outsoles of shoes and boots include rubber materials, polyurethane materials, plastic materials and thermoplastic elastomers. Rubber materials are widely used for their anti-skid and wear-resistant properties. Rubber materials are generally made of a formula composed of raw rubber, filling and reinforcement system, plasticizing system, anti-aging system, vulcanization system and other systems through a mixing and vulcanization process; among which the raw rubber system, filling and reinforcement system and plasticizing system play a key role in the anti-skid and wear-resistant properties of rubber materials.
[0004] The commonly used rubber types in the raw rubber system of the rubber outsole formula for shoes and boots are cis-1,4-dimethyl-1-butyl rubber, natural rubber, styrene-butadiene rubber, bromobutyl rubber, nitrile rubber, and carboxyl nitrile rubber; cis-1,4-dimethyl-1-butyl rubber has excellent wear resistance, excellent low-temperature performance, flexion resistance, and good elasticity, but its anti-slip performance is poor; natural rubber has excellent comprehensive mechanical properties and good wear resistance, but poor anti-slip performance; styrene-butadiene rubber is copolymerized with butadiene and styrene, and its performance is mainly determined by the content of the two components and the polymerization mode of butadiene. For example, styrene-butadiene rubber with low bound styrene content and low vinyl content has good wear resistance, but poor anti-slip performance, and styrene-butadiene rubber with high bound styrene content and high vinyl content has poor wear resistance, but excellent anti-slip performance; bromobutyl rubber has excellent damping performance, excellent gas barrier properties, good aging resistance, very poor wear resistance, and excellent anti-slip performance; the anti-slip performance of nitrile rubber is closely related to its acrylonitrile content. Styrene-butadiene rubber with high acrylonitrile content has a higher glass transition temperature and better anti-slip performance. Different types of rubber can be used in combination according to different property requirements, but the compatibility gap and co-vulcanization gap between different types of rubber often cause losses in mechanical properties and wear resistance.
[0005] Commonly used filling and reinforcement systems for rubber outsoles of shoes and boots include carbon black, white carbon black, calcium carbonate, clay, etc. Among them, carbon black is mainly used in rubber materials with high wear resistance requirements, and white carbon black is mainly used in light-colored rubber materials or rubber materials with high anti-slip requirements. However, the polar groups on the surface of white carbon black make it easy to agglomerate in rubber, which seriously affects the wear resistance and processability. Generally, physical modifiers such as polyethylene glycol or chemical modifiers such as silane coupling agents are used for modification to improve its dispersibility and binding with rubber molecular chains. The modification effect of physical modifier polyethylene glycol is limited, and silane coupling agents can achieve better modification results. However, the modification effect of silane coupling agents on white carbon black is closely related to the mixing reaction process of the rubber formula. It requires a sufficiently long reaction time within a specific temperature range to achieve a certain degree of modification on the surface of white carbon black. If the modification conditions are not suitable and the modification effect is not good, it will cause serious loss of wear resistance.
[0006] Therefore, when designing the rubber material formula, the raw rubber system and the filling system are often used in combination according to the performance requirements to meet the requirements for anti-slip and wear resistance. At present, it is necessary to develop a new rubber formula material and process, through the combination of rubber and filler modification, to improve the anti-slip performance of the rubber outsole for shoes and boots, while ensuring that the rubber material has good wear resistance, taking into account high anti-slip and high wear resistance. Summary of the invention
[0007] The purpose of the present invention is to provide a rubber material for outsoles of shoes and boots with high anti-skid and high wear resistance and a preparation method thereof. The present invention achieves both high anti-skid and high wear resistance by constructing a raw rubber system with different characteristics and good compatibility, introducing modified four-needle zinc oxide whiskers and combining high surface area precipitated silica with the modification.
[0008] To achieve the above object, the present invention adopts the following technical solution: In a first aspect, the present invention provides a rubber composition for a high-slip and high-wear-resistant outsole of shoes and boots, which is made of the following raw materials in parts by weight: Styrene-butadiene rubber A 10-20 parts; 60-80 parts of styrene-butadiene rubber B; 10-30 parts of high cis polybutadiene rubber; 50-100 parts of precipitated silica; 2,2'-methylenebis-(4-methyl-6-tert-butylphenol) 1-2 parts; Silane coupling agent 4-8 parts; Resin 5-20 parts; 5 to 20 parts of modified three-dimensional four-needle whiskers; 2-5 parts of zinc oxide; 0.5-1.5 parts of stearic acid; 1 to 2.5 parts of vulcanizing agent; 1 to 2.5 parts of N-cyclohexyl-2-benzothiazole sulfenamide; 1-2 parts of diphenylguanidine; Wherein, the glass transition temperature of the styrene-butadiene rubber A is greater than the glass transition temperature of the styrene-butadiene rubber B; The modified three-dimensional four-needle whisker is obtained by modifying the four-needle zinc oxide whisker with a modifier.
[0009] Furthermore, in the rubber composition for high-slip and high-wear-resistant outsoles for shoes and boots, the glass transition temperature of the styrene-butadiene rubber A is greater than -30°C, the combined styrene content is greater than 20%, the vinyl content is greater than 20%, the Mooney viscosity ML (1+4) at 100°C is greater than 60, and the molecular weight distribution index is less than 1.3; The styrene-butadiene rubber B has a glass transition temperature of less than -58°C, a bound styrene content of less than 25%, a vinyl content of ≤30%, a Mooney viscosity ML (1+4) at 100°C of more than 50, and a molecular weight distribution index of less than 1.3; The high cis polybutadiene rubber has a cis 1,4-butadiene content of more than 97%, a molecular weight distribution coefficient of less than 2.5, a Mooney viscosity ML (1+4) of 35 to 45 at 100° C., a trans 1,4-butadiene content of less than 2%, and a 1,2-vinyl content of less than 2%.
[0010] Furthermore, in the rubber composition for high anti-skid and high wear-resistant shoe outsole, the nitrogen adsorption specific surface area of the precipitated silica is greater than 190 m 2 / g, oil absorption value>200×10 -5 m 3 / Kg, 45μm sieve residue <0.5%, pH value 5.0~8.0; The silane coupling agent is one or a combination of any proportions of bis-[3-(triethoxysilyl)-propyl]-tetrasulfide, bis-[3-(triethoxysilyl)-propyl]-disulfide, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, γ-mercaptopropylethoxybis(propyl-hexaethoxy-siloxane), and 3-octanoylthio-1-propyltriethoxysilane; The amount of the silane coupling agent used is 8% by weight of the precipitated silica.
[0011] Furthermore, in the rubber composition for the highly anti-slip and highly wear-resistant outsoles of shoes and boots, the resin is one or a mixture of any proportions of C5 resin or its derivatives, C9 resin or its derivatives, α-methylstyrene homopolymer resin or its derivatives, dicyclopentadiene resin or its derivatives, terpene resin or its derivatives, and pinene resin or its derivatives.
[0012] Furthermore, in the rubber composition for high-slip and high-wear-resistant outsoles for shoes and boots, the modifier is any one of bis-[3-(triethoxysilyl)-propyl]-tetrasulfide, bis-[3-(triethoxysilyl)-propyl]-disulfide, and 3-octanoylthio-1-propyltriethoxysilane, or a mixture of any proportions thereof; The preparation method of the modified three-dimensional four-needle whisker comprises the following steps: 1) mixing anhydrous ethanol, water and the modifier and hydrolyzing them at 60°C to 70°C for 4h to 5h; 2) adding the dried four-needle zinc oxide crystals to the system obtained in step 1), reacting at 65°C to 75°C for 4h to 5h, and drying after the reaction is completed to obtain the modified three-dimensional four-needle whisker.
[0013] Furthermore, in the rubber composition for the outsole of highly anti-skid and highly wear-resistant shoes and boots, the zinc oxide is one or a combination of any proportions of indirect zinc oxide, active zinc oxide, and nano zinc oxide.
[0014] Furthermore, in the rubber composition for high anti-skid and high wear-resistant outsoles of shoes and boots, the C18 content of the stearic acid is 35-70%, the saponification value is 190-225 mg / g, the acid value is 190-224 mg / g, and the solidification point is greater than 52° C.; and / or, The vulcanizing agent is one of common sulfur, insoluble sulfur, sulfur masterbatch with rubber as carrier, or a combination of several of them in any proportion.
[0015] In a second aspect, the present invention provides a method for preparing the rubber composition for the outsole of a shoe with high anti-skid and high wear resistance as described in any one of the above items, characterized in that it comprises the following steps: S1, plasticizing the styrene-butadiene rubber A, the styrene-butadiene rubber B and the high-cis polybutadiene rubber; S2, adding the precipitated silica, the silane coupling agent, the diphenylguanidine and the modified three-dimensional four-needle whisker to the system obtained in step S1, and mixing them; S3, adding the resin, the stearic acid and the 2,2'-methylenebis-(4-methyl-6-tert-butylphenol) to the system obtained in step S2, mixing to obtain a masterbatch; S4, mixing the masterbatch, the vulcanizing agent, the N-cyclohexyl-2-benzothiazole sulfenamide and the zinc oxide to obtain a final rubber mix.
[0016] Furthermore, in the method for preparing the rubber composition for the outsole of high-slip and high-wear-resistant shoes and boots, in step S1, the speed of the mastication is 30 to 45 rpm, and the time is 30 to 40 seconds; In step S2, the mixing speed is 35-50 rpm, first mixing to 140-145° C., and then maintaining the temperature in the range of 140-145° C. for 4-8 minutes; In step S3, the mixing speed is 35-50 rpm, the mixing time is 20-30 s, and the debonding temperature is less than 150°C; In step S4, the mixing speed is 15-30 rpm, the mixing time is 1-2 min, and the debinding temperature is less than 100°C.
[0017] In a third aspect, the present invention provides a high-slip and high-wear-resistant footwear, comprising an outsole, wherein the outsole is made of the rubber composition for high-slip and high-wear-resistant footwear outsoles described in any one of the above items.
[0018] The present invention has the following beneficial effects: (1) In the design of the rubber formula raw rubber system, the present invention adopts different rubber types with good thermodynamic compatibility to construct a multi-component raw rubber system, wherein the rubber component styrene butadiene rubber B with a low glass transition temperature not only ensures the basic anti-slip performance, but also gives the material good wear resistance; the rubber component styrene butadiene rubber A with a high glass transition temperature gives the material good anti-slip performance; and a small amount of high cis-polybutadiene rubber is added so that the overall raw rubber system takes into account both anti-slip and wear resistance. The above three components have good compatibility, thereby avoiding the loss of wear resistance due to compatibility problems in the raw rubber system.
[0019] (2) On the basis of the traditional silica filling reinforcement system, three-dimensional four-needle whiskers are introduced to improve the anti-slip performance. In view of the poor dispersibility of the three-dimensional four-needle whiskers themselves and the poor bonding with rubber, which leads to poor wear resistance, the three-dimensional three-dimensional four-needle whiskers are surface-modified using a silane coupling agent to improve their dispersibility and bonding with rubber molecular chains. Through the chemical modification of the coupling agent, on the one hand, the hydrophobicity of the surface of the four-needle zinc oxide whiskers is improved and their agglomeration in the rubber is inhibited. On the other hand, during the vulcanization process, the silane coupling agent on the surface of the four-needle zinc oxide whiskers can react chemically with the rubber molecular chains to generate chemical bonds, thereby ensuring the dispersion of the four-needle zinc oxide whiskers and improving the bonding with the rubber molecular chains. Through the above method, the present invention takes into account both anti-slip and wear resistance.
[0020] (3) The reinforcing filler of the present invention is mainly selected from precipitated silica with high specific surface area. When the amount of silica used exceeds 50% of the raw rubber component, it is considered as high filling, which can effectively improve the anti-slip performance of the rubber material. The high specific surface area silica combined with silane chemical modification can also ensure the wear resistance of the rubber material.
[0021] Through the coordination of the above three methods, both anti-slip performance and wear resistance are achieved at a high level. DETAILED DESCRIPTION
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] As described in the background technology, the compatibility gap and co-vulcanization gap between different types of rubbers often cause losses in mechanical properties and wear resistance, and the modification effect of silane coupling agent on silica is closely related to the mixing reaction process of the rubber formula. It requires a sufficiently long reaction time within a specific temperature range to achieve a certain degree of modification of the silica surface. If the modification conditions are not suitable and the modification effect is not good, it will cause serious loss of wear resistance. How to take into account the high anti-slip and high wear resistance of rubber outsoles for shoes and boots still has certain technical difficulties.
[0024] In view of the above technical problems, the present invention provides a rubber composition for high anti-skid and high wear-resistant outsoles of shoes and boots, which is made of the following raw materials in parts by weight: 10 to 20 parts of styrene-butadiene rubber A; 60 to 80 parts of styrene-butadiene rubber B; 10 to 30 parts of high cis polybutadiene rubber; 50 to 100 parts of precipitated silica; 1 to 2 parts of 2,2'-methylenebis-(4-methyl-6-tert-butylphenol); 4 to 8 parts of silane coupling agent; 5 to 20 parts of resin; modified 5-20 parts of three-dimensional four-needle whiskers; 2-5 parts of zinc oxide; 0.5-1.5 parts of stearic acid; 1-2.5 parts of vulcanizing agent; 1-2.5 parts of N-cyclohexyl-2-benzothiazole sulfonamide; 1-2 parts of diphenylguanidine; wherein the glass transition temperature of the styrene-butadiene rubber A is greater than -30°C, and the glass transition temperature of the styrene-butadiene rubber B is less than -58°C; the modified three-dimensional four-needle whiskers are obtained by modifying four-needle zinc oxide whiskers with a modifier.
[0025] In some embodiments of the present invention, the rubber composition for the outsole of highly anti-slip and highly wear-resistant shoes and boots is made of the following raw materials in parts by weight: 10 to 20 parts of styrene butadiene rubber A; 60 to 80 parts of styrene butadiene rubber B; 10 to 30 parts of high cis polybutadiene rubber; 60 to 80 parts of precipitated silica; 1.5 parts of 2,2'-methylenebis-(4-methyl-6-tert-butylphenol); 4.8 parts of silane coupling agent; 10 to 20 parts of resin; 10 to 20 parts of modified three-dimensional four-needle whiskers; 3 parts of zinc oxide; 1 part of stearic acid; 1.1 parts of vulcanizing agent; 1.6 to 1.8 parts of N-cyclohexyl-2-benzothiazole sulfonamide; 1.4 to 2 parts of diphenyl guanidine; wherein the glass transition temperature of the styrene butadiene rubber A is greater than the glass transition temperature of the styrene butadiene rubber B; and the modified three-dimensional four-needle whiskers are obtained by modifying the four-needle zinc oxide whiskers with a modifier.
[0026] According to the present invention, styrene-butadiene rubber is a product of random copolymerization of two monomers, butadiene and styrene. The performance of styrene-butadiene rubber varies greatly with the different styrene-butadiene content and the polymerization mode of butadiene in rubber. The glass transition temperature also varies greatly. The anti-slip and wear resistance, high and low temperature performance and hysteresis loss of styrene-butadiene rubber with different styrene vinyl content are all very different, and the application scenarios may be completely different. In at least one embodiment of the present invention, the glass transition temperature of the styrene-butadiene rubber A is greater than -30°C, the combined styrene content is greater than 20%, the vinyl content is greater than 20%, the Mooney viscosity ML (1+4) 100°C is greater than 60, and the molecular weight distribution index is less than 1.3; as an example, the styrene-butadiene rubber A is Taipol 2466, and according to the product manual, its parameters are as follows: glass transition temperature -22°C, combined styrene content 21%, vinyl content 65%, Mooney viscosity ML (1+4) 100°C 75, and molecular weight distribution index 1.24. In at least one embodiment of the present invention, the glass transition temperature of the styrene-butadiene rubber B is less than -58°C, the combined styrene content is less than 25%, the vinyl content is ≤30%, the Mooney viscosity ML (1+4) 100°C is greater than 50, and the molecular weight distribution index is less than 1.3; as an example, the styrene-butadiene rubber B is Trinseo 3402, and according to the product manual, its parameters are as follows: glass transition temperature -62°C, combined styrene content 15%, vinyl content 30%, Mooney viscosity ML (1+4) 100°C 70, and molecular weight distribution index 1.28. The determination method of each parameter is as follows: glass transition temperature GB / T 29611-2013, combined styrene content GB / T 28728-2012; vinyl content GB / T 28728-2012, Mooney viscosity ML (1+4) 100°C GB / T 1232.1-2016, molecular weight distribution index SH / T 1759-2007. The present invention combines the above-mentioned styrene butadiene rubber A and styrene butadiene rubber B to improve the anti-skid and wear-resistant properties of the rubber composition. In at least one embodiment of the present invention, the cis-1,4-butadiene content of the high-cis polybutadiene rubber is greater than 97%, the molecular weight distribution coefficient is less than 2.5, the Mooney viscosity ML (1+4) 100°C is 35-45, the trans-1,4-butadiene content is less than 2%, and the 1,2-vinyl content is less than 2%; as an example, the high-cis polybutadiene rubber is Arlanxeo CB22, with a cis-1,4-butadiene content of 98%, a molecular weight distribution coefficient of 2.1, a Mooney viscosity ML (1+4) 100°C is 44, a trans-1,4-butadiene content of 1.5%, and a 1,2-vinyl content of 0.5%.The determination methods of the parameters are as follows: cis-1,4-butadiene content SH / T1727-2017, molecular weight distribution coefficient SH / T 1759-2007; vinyl content SH / T 1727-2017, Mooney viscosity ML(1+4)100°C GB / T 1232.1-2016. In the selection of raw rubber as the rubber raw material, the present invention uses raw rubbers of different types and characteristics, the components with low glass transition temperature ensure wear resistance, and the components with high glass transition temperature ensure anti-slip properties. In order to prevent the deterioration of wear resistance caused by poor compatibility or poor co-vulcanization of different rubbers, a raw rubber system with good thermodynamic compatibility is designed to ensure anti-slip properties while ensuring its wear resistance.
[0027] According to the present invention, the nitrogen adsorption specific surface area of the precipitated silica is greater than 190 m 2 / g, oil absorption value>200×10 - 5 m 3 / Kg, 45μm sieve residue <0.5%, pH value 5.0-8.0. As an example, the precipitated white carbon black is Solvay Company, brand 200MP white carbon black, and its nitrogen adsorption specific surface area is 212m 2 / g, oil absorption value is 230×10 -5 m 3 / Kg, 45μm sieve residue is 0.4%, and pH value is 7.0. The silane coupling agent is one or more of bis-[3-(triethoxysilyl)-propyl]-tetrasulfide (Si69), bis-[3-(triethoxysilyl)-propyl]-disulfide (Si75), 3-mercaptopropyltrimethoxysilane (KH580), 3-mercaptopropyltriethoxysilane (KH590), γ-mercaptopropylethoxybis(propyl-hexaethoxy-siloxane) (Si747), 3-octanoylthio-1-propyltriethoxysilane (NXT) in any proportion. The present invention uses highly filled high specific surface precipitated silica, which as a rigid particle in the anti-skid process can play a role in piercing the water film, thereby improving the anti-skid effect. The high specific surface area precipitated silica ensures the wear resistance of the rubber material through a suitable silane modification process. Specifically, the amount of the silane coupling agent used is 8% by weight of the precipitated silica.
[0028] According to the present invention, the resin is one or a mixture of any proportion of C5 resin or its derivatives, C9 resin or its derivatives, α-methylstyrene homopolymer resin or its derivatives, dicyclopentadiene resin or its derivatives, terpene resin or its derivatives, and pinene resin or its derivatives.
[0029] According to the present invention, the modifier is any one of bis-[3-(triethoxysilyl)-propyl]-tetrasulfide, bis-[3-(triethoxysilyl)-propyl]-disulfide, 3-octanoylthio-1-propyltriethoxysilane, or a mixture of any proportions thereof. In the prior art, the two-dimensional structured whiskers (such as calcium sulfate whiskers) used have poor contribution to the roughness of the outer surface of the sole due to the orientation problem of the two-dimensional structure in the rubber, and even have a side effect on anti-slip when the orientation is parallel to the sole. In the present invention, the shape of the four-needle zinc oxide whisker presents a four-dimensional needle-like structure, and has a very high modulus, providing an interface rigid contact point and increasing the surface micro-roughness during the sliding process between the rubber and the friction surface, so that it is easier to pierce the liquid film, thereby playing a role in increasing the anti-skid performance of the rubber; however, since the four-needle zinc oxide whisker belongs to an inorganic powder filler, there are a large number of polar hydroxyl groups on the surface, so that the interaction force between the whiskers is much greater than the interaction force between the whiskers and the rubber, and the compatibility with the rubber material belonging to the organic material is poor, and it is easy to agglomerate in the rubber, although it can improve the anti-skid performance of the rubber material, but due to its poor compatibility with the rubber, the wear resistance is deteriorated, so when using the four-needle zinc oxide whisker to improve the anti-skid performance, it is necessary to improve the compatibility of the four-needle zinc oxide whisker with the rubber, so as to improve the wear resistance. The chemical characteristics of the surface of the four-needle zinc oxide whisker provide the possibility of increasing the compatibility with the rubber by modification, and there are a large number of polar hydroxyl groups on its surface that can be used as modification points. The present invention uses a silane coupling agent as a modifier to modify the tetra-needle zinc oxide, thereby improving the compatibility between the tetra-needle zinc oxide and the rubber, thereby improving the wear resistance. The silane coupling agent is an amphiphilic substance, and there are two groups with different chemical properties in the molecule, one is an organic-philic group, which can react chemically with the rubber molecular chain to produce chemical bonding, and the other is an inorganic-philic group, which can react chemically with the hydroxyl group on the surface of the tetra-needle zinc oxide whisker and be coated around the crystal; the silane coupling agent is equivalent to a bridge, one end of which is connected to the tetra-needle zinc oxide whisker, and the other end is connected to the rubber molecular chain. While the tetra-needle zinc oxide whisker improves the anti-slip performance, it also improves its binding with the rubber molecule, thereby improving the wear resistance. The present invention introduces organically modified tetra-needle zinc oxide whiskers into the rubber formula, and while the tetra-needle zinc oxide whiskers improve the anti-slip performance, they are modified by the silane coupling agent to form a firm bond with the rubber molecular chain, thereby solving the problem of the tetra-needle zinc oxide whisker causing the wear resistance to deteriorate. The preparation method of the modified three-dimensional four-needle whisker comprises the following steps: 1) mixing anhydrous ethanol, water and the modifier and hydrolyzing them at 60°C to 70°C for 4h to 5h; 2) adding the dried four-needle zinc oxide crystals to the system obtained in step 1), reacting at 65°C to 75°C for 4h to 5h, and drying after the reaction is completed to obtain the modified three-dimensional four-needle whisker.The present invention modifies the four-needle zinc oxide whisker by using a silane coupling agent such as NXT. By using the silane coupling agent in the above-mentioned material, a hydrolysis reaction can occur in an aqueous solution of ethanol to generate a silanol group. The alcohol group connected to the silicon atom can form a hydrogen bond or dehydration condensation with the zinc hydroxyl group on the surface of the four-needle zinc oxide whisker to form a Si-O-Zn bond. Finally, the silane coupling agent will be fixed on the surface of the four-needle zinc oxide whisker, improve its surface hydrophobicity and the binding property with the rubber molecular chain, and finally reduce the loss of wear resistance while improving the anti-slip effect. Wherein, the mass fractions of the four-needle zinc oxide whisker, anhydrous ethanol, deionized water and silane coupling agent used in the preparation method of the modified three-dimensional four-needle whisker can be adjusted within a reasonable range under the premise of achieving the modification requirements when the experimental device is satisfied. As an example, in the hydrolysis step, the mass ratio of anhydrous ethanol and water is 40:6, and the silane coupling agent NXT is 6% of the mass of the four-needle zinc oxide whisker.
[0030] According to the present invention, the zinc oxide is one or a combination of any proportion of indirect zinc oxide, active zinc oxide, and nano zinc oxide, such as indirect zinc oxide type I produced by Oron Zinc Industry Co., Ltd.
[0031] According to the present invention, the C18 content of the stearic acid is 35-70%, the saponification value is 190-225 mg / g, the acid value is 190-224 mg / g, and the solidification point is greater than 52°C; as an example, the stearic acid is 1840 from Hangzhou Oil Chemical Company, with a C18 content of 40%, a saponification value of 210 mg / g, an acid value of 208 mg / g, and a solidification point of 56°C.
[0032] According to the present invention, the vulcanizing agent is one of common sulfur, insoluble sulfur, sulfur masterbatch with rubber as carrier, or a combination of any proportions of the above. Sulfur can be divided into common sulfur and insoluble sulfur. Common sulfur is insoluble in water, slightly soluble in ethanol and ether, and easily soluble in carbon disulfide, while insoluble sulfur is insoluble in carbon disulfide.
[0033] The present invention further provides a method for preparing the rubber composition for the high-slip and high-wear-resistant outsoles of shoes and boots as described in any of the above items, comprising the following steps: S1, plasticizing the styrene-butadiene rubber A, the styrene-butadiene rubber B and the high-cis polybutadiene rubber; S2, adding the precipitated silica, the silane coupling agent, the diphenyl guanidine and the modified three-dimensional four-needle whisker to the system obtained in step S1, and mixing them; S3, adding the resin, the stearic acid and the 2,2'-methylenebis-(4-methyl-6-tert-butylphenol) to the system obtained in step S2, and mixing them to obtain a masterbatch; S4, mixing the masterbatch, the vulcanizing agent, the N-cyclohexyl-2-benzothiazolesulfonamide and the zinc oxide to obtain a final rubber mix.
[0034] According to the present invention, in step S1, the speed of the plasticizing is 30-45rpm (such as 40rpm), the time is 30-40s (such as 35s), and it is carried out in an internal mixer; in step S2, the speed of the mixing is 35-50rpm (such as 45rpm), first mixing to 140-145°C (such as 143°C), and then keeping the temperature in the range of 140-145°C for mixing for 4-8min (such as 6min); in step S3, the speed of the mixing is 35-50rpm (such as 40rpm), the mixing time is 20-30s, and the debonding temperature is less than 150°C; in step S4, the speed of the mixing is 15-30rpm, the mixing time is 1-2min, the debonding temperature is less than 100°C, and it is carried out in an internal mixer. Among them, the mixing time in step S2 needs to ensure that the white carbon black and the silane coupling agent react fully. When the mixing time is too short, the wear resistance will be significantly deteriorated, the hardness will increase, and the mechanical properties will be deteriorated.
[0035] The present invention also protects a high-slip and high-wear-resistant footwear, including an outsole, wherein the outsole is made of the rubber composition for high-slip and high-wear-resistant footwear outsoles described in any one of the above items. In the present invention, the rubber composition introduces zinc oxide whiskers on the basis of the traditional anti-slip rubber formula to improve the surface roughness, thereby improving the anti-wet skid performance, and at the same time, the zinc oxide whiskers are modified to ensure the wear resistance. The friction between the tire and the footwear and the contact surface has both static friction and dynamic friction. The frequency of the static friction of the tire is much higher than that of the static friction of the footwear, and the tire mainly generates dynamic friction during the rolling process, while the footwear mainly generates dynamic friction during the sliding process. Therefore, the requirements for the performance of the rubber composition for footwear and the rubber composition for the tire are also different.
[0036] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.
[0037] The methods used in the following examples, unless otherwise specified, are all conventional methods, carried out according to the techniques or conditions described in the literature in the art or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.
[0038] In the following examples and comparative examples, the styrene-butadiene rubber A used was purchased from Taiwan Rubber Co., Ltd., with the brand name Taipol 2466; The styrene butadiene rubber B used was purchased from Trinseo, brand 3402; The high-cis polybutadiene rubber used was purchased from ARLANXEO, brand CB22; The precipitated silica used was purchased from Solvay, brand 200MP; The silane coupling agent used was purchased from Momentive High-Tech Materials Co., Ltd., brand NXT; The resin used was purchased from Trinseo, brand 3402; The tetrapod-shaped zinc oxide whiskers used were purchased from Shanghai Niuer Rubber & Plastic Products Co., Ltd. The modification process steps are as follows: 1) Dry the tetrapod-shaped zinc oxide whiskers in a vacuum drying oven at 115°C for 16 hours; 2) Remove the adsorbed water on the surface of the tetrapod-shaped zinc oxide whiskers; 3) Add 40g of anhydrous ethanol, 6g of deionized water, and silane coupling agent NXT (the amount is 6% of the mass of the tetrapod-shaped zinc oxide whiskers to be modified) into a flask, and hydrolyze at a temperature of 65°C for 4 hours; Add 30g of the dried tetrapod-shaped zinc oxide whiskers into a beaker and react at 70°C for 5 hours; 4) Dry the reacted tetrapod-shaped zinc oxide whiskers in a drying oven at 75°C for 24 hours to obtain modified three-dimensional tetrapod-shaped whiskers; The zinc oxide used was purchased from Aolong Zinc Company, and the model was indirect zinc oxide type I; The stearic acid used was purchased from Hangzhou Oil Chemical Company, brand 1840; The vulcanizing agent used was purchased from Kailun Chemical Company, brand IS7520; The N-cyclohexyl-2-benzothiazole sulfenamide and diphenylguanidine used were purchased from Kailun Chemical Company; The 2,2'-methylenebis-(4-methyl-6-tert-butylphenol) used was purchased from Qingdao Xunneng Technology Co., Ltd.
[0039] Example 1 This embodiment provides a rubber composition for high anti-skid and high wear-resistant shoe outsole and a preparation method thereof. The specific formula is shown in Example 1 in Table 1. The specific preparation steps are as follows: (1) Styrene butadiene rubber A, styrene butadiene rubber B and high cis polybutadiene rubber were plasticized in an internal mixer at a speed of 40 rpm and a plasticizing time of 35 s; (2) Then add precipitated silica, silane coupling agent, diphenyl guanidine, and modified three-dimensional four-needle whiskers, and mix them at a speed of 45 rpm. First, mix them to 143° C., and then keep the temperature in the range of 140-145° C. and mix them for 6 minutes; (3) Adding resin, stearic acid and 2,2'-methylenebis-(4-methyl-6-tert-butylphenol) again, mixing at a speed of 40 rpm, a mixing time of 20-30 s, and a discharge temperature of <150°C to obtain a masterbatch; (4) Mix the masterbatch, vulcanizing agent, N-cyclohexyl-2-benzothiazolesulfonamide and zinc oxide in an internal mixer at a speed of 15-30 rpm, a mixing time of 1-2 min, and a discharge temperature of less than 100° C. to obtain a final rubber mixture.
[0040] Example 2 The formula is shown in Example 2 in Table 1, and the preparation steps are the same as Example 1.
[0041] Example 3 The formula is shown in Example 3 in Table 1, and the preparation steps are the same as Example 1.
[0042] Example 4 The formula is shown in Example 4 in Table 1, and the preparation steps are the same as Example 1.
[0043] Example 5 The formula is shown in Example 5 in Table 1, and the preparation steps are the same as Example 1.
[0044] Example 6 The formula is shown in Example 6 in Table 1, and the preparation steps are the same as those in Example 1.
[0045] Example 7 The formula is shown in Example 7 in Table 1, and the preparation steps are the same as Example 1.
[0046] Comparative Example 1 The formula is shown in Comparative Example 1 in Table 2, which is different from Example 2 except that the modified three-dimensional four-needle whiskers are not added.
[0047] The specific preparation steps are as follows: (1) Styrene butadiene rubber A, styrene butadiene rubber B and high cis polybutadiene rubber were plasticized in an internal mixer at a speed of 40 rpm and a plasticizing time of 35 s; (2) Then add precipitated silica, silane coupling agent and diphenylguanidine, mix at a speed of 45 rpm, first mix to 143°C, and then keep the temperature in the range of 140-145°C for 6 minutes; (3) Adding resin, stearic acid and 2,2'-methylenebis-(4-methyl-6-tert-butylphenol) again, mixing at a speed of 40 rpm, a mixing time of 20-30 s, and a discharge temperature of <150°C to obtain a masterbatch; (4) Mix the masterbatch, vulcanizing agent, N-cyclohexyl-2-benzothiazolesulfonamide and zinc oxide in an internal mixer at a speed of 15-30 rpm, a mixing time of 1-2 min, and a discharge temperature of less than 100° C. to obtain a final rubber mixture.
[0048] Comparative Example 2 The formula is shown in Comparative Example 2 in Table 2. Compared with Example 7, only the modified three-dimensional four-needle whiskers are replaced by unmodified three-dimensional four-needle whiskers.
[0049] The specific preparation method is as follows: (1) Styrene butadiene rubber A, styrene butadiene rubber B and high cis polybutadiene rubber were plasticized in an internal mixer at a speed of 40 rpm and a plasticizing time of 35 s; (2) Then, precipitated silica, silane coupling agent, diphenylguanidine, and unmodified three-dimensional four-needle whiskers were added and mixed at a speed of 45 rpm. The mixture was first mixed to 143° C., and then mixed at a temperature of 140-145° C. for 6 minutes. (3) Adding resin, stearic acid and 2,2'-methylenebis-(4-methyl-6-tert-butylphenol) again, mixing at a speed of 40 rpm, a mixing time of 20-30 s, and a discharge temperature of <150°C to obtain a masterbatch; (4) Mix the masterbatch, vulcanizing agent, N-cyclohexyl-2-benzothiazolesulfonamide and zinc oxide in an internal mixer at a speed of 15-30 rpm, a mixing time of 1-2 min, and a discharge temperature of less than 100° C. to obtain a final rubber mixture.
[0050] Comparative Example 3 The formula is shown in Comparative Example 3 in Table 2. Compared with Example 5, only styrene butadiene rubber B is replaced by styrene butadiene rubber A.
[0051] The specific preparation method is as follows: (1) Styrene-butadiene rubber A and high-cis polybutadiene rubber were plasticized in an internal mixer at a speed of 40 rpm and a plasticizing time of 35 s; (2) Then add precipitated silica, silane coupling agent, diphenyl guanidine, and modified three-dimensional four-needle whiskers, and mix them at a speed of 45 rpm. First, mix them to 143° C., and then keep the temperature in the range of 140-145° C. and mix them for 6 minutes; (3) Adding resin, stearic acid and 2,2'-methylenebis-(4-methyl-6-tert-butylphenol) again, mixing at a speed of 40 rpm, a mixing time of 20-30 s, and a discharge temperature of <150°C to obtain a masterbatch; (4) Mix the masterbatch, vulcanizing agent, N-cyclohexyl-2-benzothiazolesulfonamide and zinc oxide in an internal mixer at a speed of 15-30 rpm, a mixing time of 1-2 min, and a discharge temperature of less than 100° C. to obtain a final rubber mixture.
[0052] Comparative Example 4 The formula is shown in Comparative Example 4 in Table 2, in which only the styrene-butadiene rubber A is omitted compared with Example 3.
[0053] The specific preparation method is as follows: (1) Plasticizing styrene butadiene rubber B and high cis polybutadiene rubber in an internal mixer at a speed of 40 rpm and a plasticizing time of 35 s; (2) Then add precipitated silica, silane coupling agent, diphenyl guanidine, and modified three-dimensional four-needle whiskers, and mix them at a speed of 45 rpm. First, mix them to 143° C., and then keep the temperature in the range of 140-145° C. and mix them for 6 minutes; (3) Adding resin, stearic acid and 2,2'-methylenebis-(4-methyl-6-tert-butylphenol) again, mixing at a speed of 40 rpm, a mixing time of 20-30 s, and a discharge temperature of <150°C to obtain a masterbatch; (4) Mix the masterbatch, vulcanizing agent, N-cyclohexyl-2-benzothiazolesulfonamide and zinc oxide in an internal mixer at a speed of 15-30 rpm, a mixing time of 1-2 min, and a discharge temperature of less than 100° C. to obtain a final rubber mixture.
[0054] Comparative Example 5 The formula is shown in Comparative Example 5 in Table 2, which is consistent with Example 4 in formula composition and is compared in preparation process.
[0055] The specific preparation steps are as follows: (1) Styrene butadiene rubber A, styrene butadiene rubber B and high cis polybutadiene rubber were plasticized in an internal mixer at a speed of 40 rpm and a plasticizing time of 35 s; (2) Then add precipitated silica, silane coupling agent, diphenyl guanidine, and modified three-dimensional four-needle whiskers, and mix them at a speed of 45 rpm. First, mix them to 143° C., and then keep the temperature in the range of 140-145° C. and mix them for 2 minutes; (3) Adding resin, stearic acid and 2,2'-methylenebis-(4-methyl-6-tert-butylphenol) again, mixing at a speed of 40 rpm, a mixing time of 20-30 s, and a discharge temperature of <150°C to obtain a masterbatch; (4) Mix the masterbatch, vulcanizing agent, N-cyclohexyl-2-benzothiazolesulfonamide and zinc oxide in an internal mixer at a speed of 15-30 rpm, a mixing time of 1-2 min, and a discharge temperature of less than 100° C. to obtain a final rubber mixture.
[0056] Table 1 Raw materials and composition of Examples 1-7 (parts by mass)
[0057] Table 2 Raw materials and composition of comparative examples 1-5 (parts by mass)
[0058] Performance Testing The mechanical properties, DIN wear and friction coefficient of the above-mentioned Examples 1-7 and Comparative Examples 1-5 were tested.
[0059] The Shore A hardness test is carried out in accordance with the requirements of GB / T 531.1-2008.
[0060] DIN abrasion test is carried out according to the requirements of GB / T 9867-2008.
[0061] The friction coefficient is tested according to GB / T 3903.6-2017, the shoe size is 265, the experimental medium is grade 3 water, and the test interface is ceramic tile.
[0062] The test results are shown in Tables 3 to 5.
[0063] Table 3 Shore A hardness and mechanical properties test table of Examples 1-7 and Comparative Examples 1-5
[0064] Table 4 DIN abrasion energy test table of Examples 1-7 and Comparative Examples 1-5
[0065] Table 5 Friction coefficient test table of Examples 1-7 and Comparative Examples 1-5
[0066] Compared with the rubber composition shown in Comparative Example 1, Example 2 is added with modified three-dimensional four-needle whiskers modified by silane, while no modified three-dimensional four-needle whiskers are added in Comparative Example 1. From the comparison results of Example 2 and Comparative Example 1 in Tables 3 to 5, it can be seen that the static friction coefficient and dynamic friction coefficient of Example 2 are significantly improved, wherein the dynamic friction coefficient is improved by up to 40%, which is mainly due to the fact that the modified three-dimensional four-needle whiskers are modified zinc oxide whiskers, presenting a three-dimensional structure, and there is no orientation problem similar to that of fibers when dispersed in rubber, that is, no matter how the modified zinc oxide whiskers are dispersed, one end of the rubber needle will face the rubber contact surface; therefore, when the rubber slides on the interface with liquid, the rubber needles of the four-needle zinc oxide whiskers will pierce the water film faster, so that the friction of the rubber at the slippery interface will transition from elastic fluid dynamic lubrication to interface lubrication faster; the friction force of interface lubrication is greater than that of fluid dynamic lubrication, so the modified three-dimensional four-needle whiskers have excellent friction coefficients; and because the whiskers have been surface-silane modified, their DIN wear index is still maintained at a high level.
[0067] Compared with the rubber composition shown in Comparative Example 2, Example 7 uses modified three-dimensional four-needle whiskers, while the comparative example uses unmodified three-dimensional four-needle whiskers. From the comparison results of Example 7 and Comparative Example 2 in Tables 3 to 5, it can be seen that the dynamic and static friction coefficients of Example 7 and Comparative Example 2 do not change much, but the DIN wear of Comparative Example 2 is significantly worse, and the DIN wear of Example 7 is 77 mm. 3, the DIN wear of comparative example 2 is 146mm 3 Although the tetrapod-shaped zinc oxide whisker can improve the anti-skid performance, it is an inorganic substance and contains a large number of polar hydroxyl groups on the surface, which have poor bonding with non-polar rubber molecules, resulting in a sharp deterioration in wear resistance. In view of the characteristics of the polar hydroxyl groups on the surface of the tetrapod-shaped zinc oxide, the present invention uses a silane coupling agent to modify its surface, which can improve the dispersibility of the zinc oxide whisker and inhibit its agglomeration. At the same time, the other end of the silane coupling agent can form a chemical bond with the rubber molecular chain during the vulcanization reaction, so that the tetrapod-shaped zinc oxide is firmly bonded to the rubber molecular chain, which can ultimately effectively improve the wear resistance, and ensure high wear resistance while achieving high anti-skid performance.
[0068] Compared with the rubber composition shown in Comparative Example 3, the raw rubber system of the rubber composition shown in Example 5 includes 100 parts by mass of styrene-butadiene rubber A, styrene-butadiene rubber B and high-cis polybutadiene rubber, while the raw rubber system of the rubber composition shown in Comparative Example 3 includes 100 parts by mass of styrene-butadiene rubber A and high-cis polybutadiene rubber, and Comparative Example 3 does not contain styrene-butadiene rubber B. From the comparison results of Example 5 and Comparative Example 3 in Tables 3 to 5, it can be seen that the friction coefficient of Comparative Example 3 is slightly higher than that of Example 5, and there is no obvious difference in the friction coefficient; however, the DIN wear of Comparative Example 3 is much worse than that of Example 5, and the DIN wear of Comparative Example 3 is 150 mm. 3 , the DIN wear of Example 5 is 70 mm 3 The raw rubber system of the rubber composition of Example 5 achieves both anti-slip and wear resistance by combining rubbers of different properties and types.
[0069] Compared with the rubber composition shown in Comparative Example 4, the raw rubber system of the rubber composition shown in Example 3 includes styrene butadiene rubber A, styrene butadiene rubber B and high cis polybutadiene rubber in a total of 100 parts by mass, while the raw rubber system of the rubber composition shown in Comparative Example 4 includes styrene butadiene rubber B and high cis polybutadiene rubber in a total of 100 parts by mass, and Comparative Example 4 does not contain styrene butadiene rubber A. Although the wear resistance of Comparative Example 4 is maintained at a high level (DIN wear 52 mm 3 ), but its friction coefficient has declined significantly.
[0070] Compared with the rubber composition shown in Comparative Example 5, the raw materials and composition of the rubber composition shown in Example 4 are the same as those of Comparative Example 5, but the two have differences in preparation process. Comparative Example 5 is mixed in the range of 140-145°C for 2 minutes, while the embodiment is mixed in the range of 140-145°C for 6 minutes. The wear resistance of Comparative Example 5 is significantly deteriorated, the hardness is increased, the mechanical properties are deteriorated, and the anti-slip performance is not significantly changed. This is because the modification time of Comparative Example 5 is short, the reaction of white carbon black and silane coupling agent is not sufficient, which makes white carbon black more likely to flocculate, resulting in significantly deteriorated wear resistance, increased hardness, and deteriorated mechanical properties; the insufficient reaction of white carbon black and silane reduces the reinforcing effect of white carbon black.
[0071] In embodiments 1-7 of the present invention, styrene-butadiene rubber A, styrene-butadiene rubber B and high cis-polybutadiene rubber are used to construct a raw rubber system that is both anti-skid and wear-resistant; four-needle zinc oxide whiskers are introduced and surface silane modified to greatly improve the anti-skid performance while ensuring that the material has a high level of wear resistance; among the white carbon black commonly used in anti-skid rubber materials, high specific surface area precipitated white carbon black is selected and highly filled, and modified with a silane coupling agent to further consolidate the anti-skid and wear-resistant properties; through the above three combined designs, compared with the existing traditional sole rubber materials for shoes and boots, the present invention simultaneously ensures high anti-skid performance and high wear resistance.
[0072] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, can implement the present invention in a wider range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principle of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departing from the disclosed scope in the application and the changes made with conventional techniques known in the art.
Claims
1. A rubber composition for high-slip and high-wear-resistant outsoles of shoes and boots, characterized in that: Made from the following raw materials in parts by weight: Styrene-butadiene rubber A 10-20 parts; 60-80 parts of styrene-butadiene rubber B; 10-30 parts of high cis polybutadiene rubber; 50-100 parts of precipitated silica; 2,2'-methylenebis-(4-methyl-6-tert-butylphenol) 1-2 parts; Silane coupling agent 4-8 parts; Resin 5-20 parts; 5 to 20 parts of modified three-dimensional four-needle whiskers; 2-5 parts of zinc oxide; 0.5-1.5 parts of stearic acid; 1 to 2.5 parts of vulcanizing agent; 1 to 2.5 parts of N-cyclohexyl-2-benzothiazole sulfenamide; 1-2 parts of diphenylguanidine; Wherein, the glass transition temperature of the styrene-butadiene rubber A is greater than the glass transition temperature of the styrene-butadiene rubber B; The modified three-dimensional four-needle whisker is obtained by modifying the four-needle zinc oxide whisker with a modifier.
2. The rubber composition for high-slip and high-wear-resistant outsoles of shoes and boots according to claim 1, characterized in that: The styrene-butadiene rubber A has a glass transition temperature of >-30°C, a combined styrene content of >20%, a vinyl content of >20%, a Mooney viscosity ML (1+4) of 100°C of >60, and a molecular weight distribution index of <1.3; The styrene-butadiene rubber B has a glass transition temperature of less than -58°C, a bound styrene content of less than 25%, a vinyl content of ≤30%, a Mooney viscosity ML (1+4) at 100°C of more than 50, and a molecular weight distribution index of less than 1.3; The high cis polybutadiene rubber has a cis 1,4-butadiene content of more than 97%, a molecular weight distribution coefficient of less than 2.5, a Mooney viscosity ML (1+4) of 35 to 45 at 100° C., a trans 1,4-butadiene content of less than 2%, and a 1,2-vinyl content of less than 2%.
3. The rubber composition for high-slip and high-wear-resistant outsoles of shoes and boots according to any one of claims 1-2, characterized in that: The nitrogen adsorption specific surface area of the precipitated silica is > 190 m 2 / g, oil absorption value>200×10 -5 m 3 / Kg, 45μm sieve residue <0.5%, pH value 5.0~8.0; The silane coupling agent is one or a combination of any proportions of bis-[3-(triethoxysilyl)-propyl]-tetrasulfide, bis-[3-(triethoxysilyl)-propyl]-disulfide, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, γ-mercaptopropylethoxybis(propyl-hexaethoxy-siloxane), and 3-octanoylthio-1-propyltriethoxysilane; The amount of the silane coupling agent used is 8% by weight of the precipitated silica.
4. The rubber composition for high skid resistance and high wear resistance outsole of footwear according to any one of claims 1 to 3, characterized in that: The resin is one of C5 resin or its derivatives, C9 resin or its derivatives, α-methylstyrene homopolymer resin or its derivatives, dicyclopentadiene resin or its derivatives, terpene resin or its derivatives, and pinene resin or its derivatives, or a mixture of any proportions of the above.
5. The rubber composition for high-slip and high-wear-resistant outsoles of shoes and boots according to any one of claims 1 to 4, characterized in that: The modifier is any one of bis-[3-(triethoxysilyl)-propyl]-tetrasulfide, bis-[3-(triethoxysilyl)-propyl]-disulfide, 3-octanoylthio-1-propyltriethoxysilane, or a mixture of any proportions thereof; The preparation method of the modified three-dimensional four-needle whisker comprises the following steps: 1) mixing anhydrous ethanol, water and the modifier and hydrolyzing them at 60°C to 70°C for 4h to 5h; 2) adding the dried four-needle zinc oxide crystals to the system obtained in step 1), reacting at 65°C to 75°C for 4h to 5h, and drying after the reaction is completed to obtain the modified three-dimensional four-needle whisker.
6. The rubber composition for high skid resistance and high wear resistance outsole of footwear according to any one of claims 1 to 5, characterized in that: The zinc oxide is one of indirect zinc oxide, active zinc oxide, and nano zinc oxide, or a combination of several of them in any proportion.
7. The rubber composition for high skid resistance and high wear resistance outsole of footwear according to any one of claims 1 to 6, characterized in that: The stearic acid has a C18 content of 35-70%, a saponification value of 190-225 mg / g, an acid value of 190-224 mg / g, and a solidification point of >52°C; and / or The vulcanizing agent is one of common sulfur, insoluble sulfur, sulfur masterbatch with rubber as carrier, or a combination of several of them in any proportion.
8. The method for preparing the rubber composition for high skid resistance and high wear resistance outsole of footwear according to any one of claims 1 to 7, characterized in that: The steps include: S1, plasticizing the styrene-butadiene rubber A, the styrene-butadiene rubber B and the high-cis polybutadiene rubber; S2, adding the precipitated silica, the silane coupling agent, the diphenylguanidine and the modified three-dimensional four-needle whisker to the system obtained in step S1, and mixing them; S3, adding the resin, the stearic acid and the 2,2'-methylenebis-(4-methyl-6-tert-butylphenol) to the system obtained in step S2, mixing to obtain a masterbatch; S4, mixing the masterbatch, the vulcanizing agent, the N-cyclohexyl-2-benzothiazole sulfenamide and the zinc oxide to obtain a final rubber mix.
9. The method for preparing the rubber composition for high-slip and high-wear-resistant outsoles of shoes and boots according to claim 8, characterized in that: In step S1, the speed of the plasticating is 30-45 rpm, and the time is 30-40 s; In step S2, the mixing speed is 35-50 rpm, first mixing to 140-145° C., and then maintaining the temperature in the range of 140-145° C. for 4-8 minutes; In step S3, the mixing speed is 35-50 rpm, the mixing time is 20-30 s, and the debonding temperature is less than 150°C; In step S4, the mixing speed is 15-30 rpm, the mixing time is 1-2 min, and the debinding temperature is less than 100°C.
10. A highly anti-skid and wear-resistant shoe, comprising an outsole, characterized in that: The outsole is made of the rubber composition for high-slip and high-wear-resistant outsoles for shoes and boots according to any one of claims 1-7.